Effects of English Film Subtitle on the Vocabulary Level of Grade-11 Students in a private school in Sipocot, Camarines Sur - Monida, Dimple C.; Bandojo, Melve D.; Panopio, Aira G.; Rili, Juan Jose V.; Valleno, Andrew F.; Mirate, Theodoro Jan; Ocampo, Darrel M. (Program Studi Pendidikan Bahasa Inggris, 2024)
This study aimed to determine the effects of reading subtitles on the vocabulary level of Grade-11 students in a private school in Sipocot, Camarines Sur. The study employed a pre-experimental design with static group comparison and descriptive correlational methods. The data gathering tools used were a survey questionnaire and a researcher-made test. The test was used to assess the vocabulary level of the respondents. The study found that there was a significant difference in the language proficiency of respondents who read subtitles and those who did not, in terms of vocabulary, form, meaning, and use. The respondents who read subtitles demonstrated a higher level of language proficiency in vocabulary compared to those who did not read subtitles. The study also found that there was no significant relationship between the extent of reading subtitles and vocabulary level in terms of form and meaning, but there was a significant relationship in terms of use only. Based on the findings, the study concluded that reading subtitles while watching English films can expand vocabulary level for further purposes.